STRATEGIES FOR DEVELOPING THE POTENTIAL OF VILLAGE TOURISM IN GUNUNGSARI AND KEDUMULYO VILLAGES, PATI REGENCY - Okta Yuripta Syafitri; Mohamad Soleh Nurzaman; Aria Ganna Henryanto (Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to explore and develop the tourism potential of Gunungsari and Kedumulyo Villages in Pati Regency to enhance local welfare and address challenges related to poverty and inequality. By employing a SWOT analysis, the research identifies the strengths, weaknesses, opportunities, and threats associated with tourism development in these villages. The study adopts a mixed-methods approach, combining qualitative assessments of local conditions with quantitative evaluations through the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The findings reveal that Gunungsari Village, with IFAS and EFAS scores of 3.75 and 3.64 respectively, exhibits a more effective tourism development strategy compared to Kedumulyo Village, which scores 3.42 for IFAS and 3.34 for EFAS. The results suggest that Gunungsari Village should pursue a Weakness-Opportunity (WO) Strategy, leveraging its strengths to overcome weaknesses and capitalize on opportunities. Conversely, Kedumulyo Village is recommended to adopt a Weakness-Threat (WT) Strategy to mitigate threats while addressing its weaknesses. These strategic recommendations are crucial for transforming these villages into developed or independent entities with sustainable tourism practices.